Molecular Tuning of Filamin A Activities in the Context of Adhesion and Migration - Lamsoul, Isabelle; Dupré, Loïc; Lutz, Pierre G. (Frontiers in Cell and Developmental Biology, 2020)
The dynamic organization of actin cytoskeleton meshworks relies on multiple actin-binding proteins endowed with distinct actin-remodeling activities. Filamin A is a large multi-domain scaffolding protein that cross-links actin filaments with orthogonal orientation in response to various stimuli. As such it plays key roles in the modulation of cell shape, cell motility, and differentiation throughout development and adult life. The essentiality and complexity of Filamin A is highlighted by mutations that lead to a variety of severe human disorders affecting multiple organs. One of the most conserved activity of Filamin A is to bridge the actin cytoskeleton to integrins, thereby maintaining the later in an inactive state. In this review, we here review the numerous mechanisms cells have developed to adjust Filamin A content and activity and focus on the function of Filamin A as a gatekeeper to integrin activation and associated adhesion and motility.